Hubungan Academic Self-Efficacy dan Academic Stress pada Mahsiswa S1 Tingkat Akhir Unisba - Aqyla Halwa Andhina Rahmanda; Sulisworo Kusdiyati (Bandung Conference Series: Psychology Science, 2023)
Abstract. Academic stress is one of the phenomena experienced by students who are working on their thesis. Academic Stress is a combination of several academic demands that exceed the strength or availability of someone's resources to get through it (Wilks, 2008). Academic Self-Efficacy is one of the factors that can affect Academic Stress (Oon, 2007). The purpose of this study is to see if there is a relationship between Academic Self - Efficacy and Academic Stress in final year undergraduate students of Unisba who are working on their thesis. This research approach is quantitative research and uses correlational methods. The research was conducted on 378 active final year undergraduate students of Unisba who were working on their thesis using quota sampling technique. The measuring instrument used is the Academic Self-Efficacy Scale compiled by Zajacova et al., (2005) which has been adapted into Indonesian by Arlinkasari & Zakiah (2017). The Academic Stress measuring instrument used in this study is the Student-Life Stress Inventory academic stress scale from Gadzella, B. M. (1994) which has been adapted into Indonesian by Praghlopati et al (2021). The results showed that there is a significant negative relationship between academic self-efficacy and academic stress (R Square = 0.02; Sig. 0.00). This means that the higher the academic self-efficacy of students, the lower they will tend to experience academic stress. Abstrak. Academic stress merupakan salah satu fenomena yang dialami mahasiswa yang sedang mengerjakan skripsi. Academic Stress merupakan suatu perpaduan dari beberapa tuntutan akademik yang melebihi kekuatan atau ketersediaan sumber daya seseorang untuk melewatinya (Wilks, 2008). Academic Self – Efficacy merupakan salah satu faktor yang dapat mempengaruhi Academic Stress (Oon, 2007). Tujuan penelitian ini untuk melihat apakah terdapat hubungan antara Academic Self – Efficacy dan Academic Stress pada mahasiswa S1 tingkat akhir Unisba yang sedang mengerjakan skripsi. Pendekatan penelitian ini adalah penelitian kuantitatif dan menggunakan metode korelasional. Penelitian dilakukan pada 378 mahasiswa aktif S1 tingkat akhir Unisba yang sedang mengerjakan skripsi dengan menggunakan teknik quota sampling. Alat ukur yang digunakan yaitu Academic Self-Efficacy Scale yang disusun oleh Zajacova et al., (2005) yang sudah diadaptasi ke dalam bahasa Indonesia oleh Arlinkasari & Zakiah (2017). Alat ukur Academic Stress yang digunakan dalam penelitian ini adalah skala stress akademik Student-Life Stress Inventory dari Gadzella, B. M. (1994) yang sudah diadaptasi ke dalam Bahasa Indonesia oleh Praghlopati et al (2021). Hasil penelitian menunjukkan bahwa terdapat hubungan yang negative signifikan antara academic self – efficacy dan academic stress (R Square = 0.02; Sig. 0,00). Artinya semakin tinggi academic self – efficacy mahasiswa maka mereka akan cenderung lebih rendah untuk mengalami academic stress.